BUSCA DE SUBSTÂNCIAS COM ATIVIDADE ANTIBACTERIANA NA ESPÉCIE LUDWIGIA LAGUNAE ONAGRACEAE - FREITAS, thiago Vilela de; MOTA, Jeferson Moraes; MARQUES, Maria Carolina Silva; GARCEZ, Walmir Silva; SOARES, Luzinátia Ramos (ANAIS DO ENIC, 2020)
-